X‐linked inhibitor of apoptosis single nucleotide polymorphisms and copy number variation are not risk factors for asthma. Issue 4 (25th April 2013) - Roscioli, Eugene; Hamon, Rhys; Ruffin, Richard E.; Zalewski, Peter; Grant, Janet; Lester, Susan
Abstract Background and objective Aberrant apoptosis in asthma contributes to airway inflammation. Early apoptosis and fragility of airway epithelial cells and delayed apoptosis of inflammatory lymphocytes can cooperate to increase airway inflammation. In this study, single nucleotide polymorphisms (SNPs) and copy number variation (CNV) in the Baculoviral inhibitor of apoptosis protein repeat‐containing 4 (BIRC4) gene (which encodes X‐linked inhibitor of apoptosis protein) were evaluated for associations with asthma. Methods Asthma cases (n = 203) were identified from Caucasian cohort participants in the North West Adelaide Health Study and matched with 198 controls. Asthma status was defined using self‐report of doctor‐diagnosed asthma, in conjunction with spirometry and bronchodilator response. Seven SNPs, which spanned the entire BIRC4 gene, were selected for the study on the basis of a haplotype tagging approach. SNPs genotyping was performed on the SEQUENOM MassARRAY iPLEX Gold platform, and genotyping success rate was > 98%. BIRC4 gene CNV was measured using a duplex Taqman qPCR assay, with RNAseP as the reference gene. Alleles and haplotype associations were analysed by logistic regression, assuming an additive genetic model, and adjusted for gender and atopy. Results BIRC4 gene copy number was determined entirely by gender. All SNPs were in Hardy–Weinberg equilibrium for both case and control females. BIRC4 allele and haplotype frequencies were comparable between asthma cases and controls. Conclusions There is no evidence of CNV in BIRC4, and BIRC4 is not a susceptibility gene for asthma.